Workforce Needs Analysis Through Lean Organizational Structure - Suworo; Chotamul Fajri; Sairin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to analyze workforce requirements in supporting the implementation of a lean organizational structure at PT Megatama Abadi IRS, Serang, Banten. Increasing business competition requires organizations to optimize human resources without reducing organizational effectiveness. This study employed a descriptive qualitative approach using interviews, observations, and documentation. Informants consisted of HR managers, operational managers, supervisors, and employees from several functional divisions. Data were analyzed using the Miles and Huberman interactive analysis model through data reduction, data display, and conclusion drawing. The findings indicate that the company has implemented a relatively lean organizational structure characterized by simplified coordination, reduced bureaucracy, and multitasking practices among employees. Workforce planning is determined based on project volume, work complexity, project deadlines, and employee competencies. The implementation of a lean organizational structure has improved coordination efficiency, accelerated decision-making, reduced operational costs, and enhanced organizational productivity. However, several challenges remain, including workload imbalance, increased work stress, employee fatigue, and dependence on highly competent personnel. Therefore, periodic workload evaluation, clearer job descriptions, competency development, and continuous training programs are necessary to ensure that organizational efficiency is balanced with employee well-being. The study contributes to the human resource management literature by demonstrating that lean organizational structures should be supported by systematic workforce planning to achieve sustainable organizational performance.